(untitled) (International relations and international law Journal, 2016)
Development of trade relations is a major component of the Euro-Mediterranean cooperation EU aimed at deepening regional integration through trade liberalization and the creation of a free trade zone. Trade plays a primary role in stimulating economic growth, improving living standards and per capita income and therefore reducing migration because there is a clear link between migration and quality of life. Trade plays a primary role in stimulating economic growth, improving living standards and per capita income and therefore reducing migration because there is a clear link between migration and quality of life. For forty years, trade is the oldest and most successful integrated EU policy tool. Currently the trade policy of the EU is based on Art. 131-134 of the Treaty establishing of the EU. Its main goals are the progressive abolition of restrictions on international trade and the lowering of customs tariffs. EU formulated its overall policy towards the southern Mediterranean countries, including trade, back in the 70-s., but then signed the first partnership and trade agreements with these countries. All EU Association Agreements with the southern partners, being the basis for the development of trade relations, called for the creation of the Euro-Mediterranean free trade area over a transitional period of 12 years, as well as the progressive abolition of customs duties on EU exports of industrial products in exchange for already provided free access of finished products to EU markets. The EU is the main trading partner of the South Mediterranean countries, but trade between the two regions continues to be asymmetric, static and imbalanced.